Cryogenic treatment of uddelholm orvar 2M tool steel - Τσαρουχά, Ανθή (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Θαλάσσιων Κατασκευών. Εργαστήριο Ναυπηγικής Τεχνολογίας, 2018)
The present thesis presents the results in microstructure and mechanical properties of Orvar 2M tool steel after cryogenic treatment